Hybrid Spectral Difference Methods for Elliptic Equations on Exterior Domains with the Discrete Radial Absorbing Boundary Condition - Jeon, Youngmok (Journal of Scientific Computing, 2018)
The hybrid spectral difference methods (HSD) for the Laplace and Helmholtz equations in exterior domains are proposed. We consider the fictitious domain method with the absorbing boundary conditions (ABCs). The HSD method is a finite difference version of the hybridized Galerkin method, and it consists of two types of finite difference approximations; the cell finite difference and the interface finite difference. The fictitious domain is composed of two subregions; the Cartesian grid region and the boundary layer region in which the radial grid is imposed. The boundary layer region with the radial grid makes it easy to implement the discrete radial ABC. The discrete radial ABC is a discrete version of the Bayliss–Gunzburger–Turkel ABC without pertaining any radial derivatives. Numerical experiments confirming efficiency of our numerical scheme are provided.
Keywords: Absorbing boundary condition; Boundary-layer regions; Fictitious domain method; Fictitious domains; Finite difference approximations; Hybrid difference; Numerical experiments; Spectral difference methods; Absorbing boundary condition; Cell finite difference; Helmholtz equation; Hybrid difference; Interface finite difference